Metabolic reprogramming and renal fibrosis: what role might Chinese medicine play? - Weili Wang; Rong Dai; Meng Cheng; Yizhen Chen; Yilin Gao; Xin Hong; Wei Zhang; Yiping Wang; Lei Zhang (BMC, 2024)
Abstract Metabolic reprogramming is a pivotal biological process in which cellular metabolic patterns change to meet the energy demands of increased cell growth and proliferation. In this review, we explore metabolic reprogramming and its impact on fibrotic diseases, providing a detailed overview of the key processes involved in the metabolic reprogramming of renal fibrosis, including fatty acid decomposition and synthesis, glycolysis, and amino acid catabolism. In addition, we report that Chinese medicine ameliorates renal inflammation, oxidative stress, and apoptosis in chronic kidney disease by regulating metabolic processes, thereby inhibiting renal fibrosis. Furthermore, we reveal that multiple targets and signaling pathways contribute to the metabolic regulatory effects of Chinese medicine. In summary, this review aims to elucidate the mechanisms by which Chinese medicine inhibits renal fibrosis through the remodeling of renal cell metabolic processes, with the goal of discovering new therapeutic drugs for treating renal fibrosis.